Under-Reporting of energy intake in elderly Australian women is associated with a higher body mass index - Meng, Xingqiong; Kerr, Deborah; Zhu, K.; Devine, A.; Solah, Vicky; Wright, Janine; Binns, Colin; Prince, R. (Editions S E R D I, 2013)
Design: Dietary intake was assessed using a 3-day weighed food record. Protein intake was validated by 24-hour urinary nitrogen. To examine under-reporting, participants were grouped according to their energy intake and compared to the Goldberg cut-off equation. Logistic regression was performed to assess the influence of body mass index (BMI) and social-demographic factors on under-reporting. Setting: Community dwelling elderly women from Perth, Western Australia. Participants: 217 elderly women aged 70–80 years. Results: Under-reporters had a higher physical activity level (p<0.001) compared with acceptable-reporters. The under-reporters also had a higher body weight (p=0.006), body mass index (BMI) (p=0.001), waist (p=0.011), hip circumference (p<0.001), whole body fat mass (p<0.001) and percentage body fat (p<0.001) than acceptable-reporters. Under-reporters had a significantly lower intakes of protein, fat, carbohydrate and alcohol (p<0.001) and fewer reported food items, compared with acceptable reporters. However, 24-hour urinary nitrogen was only marginally different between the two groups (p=0.053). Participants with a higher BMI were more likely to under-report their energy intake (BMI=25–29.9: odds ratio=2.98[95% CI=1.46–6.09]; BMI≥30: 5.84[2.41–14.14]). Conclusion: Under-reporting energy intake in elderly women was associated with a higher BMI, body fat and higher self-reported physical activity levels. A higher BMI (≥25) appears to be most significant factor in determining if elderly women will underreport their food intake and may be related to body image. These results have implications for undertaking surveys of food intake in elderly women.